Effect of resistance training programs differing in set structure on muscular hypertrophy and performance in untrained young men - Mao, Jun; Wang, Tianjiao; Wang, Yidan; Kuan, Garry (Frontiers in Physiology, 2023)
Abstract Purpose: This study aimed to compare the effects on muscle hypertrophy and muscular performance of two resistance training (RT) programs that differed only in set structure: traditional set structure (TS) vs. rest redistribution set structure (RR). Methods: Thirty untrained young men were pair-matched and randomly assigned to a TS (n =15) or an RR (n =15) protocol based on individual baseline measures. Participants trained for eight weeks using the same total body RT routines performed twice weekly. The TS protocol comprised four sets of 10 repetitions per exercise with 120-second interset rest, and the RR involved eight sets of five repetitions per exercise with 51-second interset rest. Participants were tested pre- and post-intervention for body composition, regional muscle thickness, upper- and lower-body muscle maximal strength (1-repetition maximum [1RM] ), mean power output and velocity at 75% 1RM and muscular endurance (repetitions to failure at 70% 1RM). Results: Compared to baseline, both groups exhibited equally significantly decreased body fat mass (p < 0.05), increased fat-free mass (p < 0.001), muscle thickness (p < 0.05), upper and lower-body muscular maximal strength (p < 0.001) and endurance performance (p < 0.001). However, both groups only increase the lower-body power output (p < 0.001) but not the upper-body (p > 0.05). No significant differences existed between groups for all measurements (p > 0.05). Conclusions: These results suggest that RR and TS groups have similar effects for improving muscle hypertrophy and performance in untrained young men.